¿Qué nos hubiera contestado Capablanca a la pregunta, es el ajedrez un deporte? / What would Capablanca have answered to the question, is chess a sport? - Uvencio José Blanco-Hernández (Universidad de Camagüey Ignacio Agramonte Loynaz, 2020)
When dealing with chess as a sport, we will first have to analyse a key question - in what sense is chess a sport? It is important to remember that chess was officially recognized - as a sport - and the International Chess Federation (FIDE), as its governing body, by the International Olympic Committee at its general assembly held in South Korea in 1999. This decision was based on a series of reports and research compiled by FIDE and the IOC itself, which point to chess as a sport because it meets a number of basic requirements. So a longstanding discussion in chess, whether chess is a sport or not, has for 20 years now decided in favour of the fact that the millenary game of chess is indeed recognized as a sporting activity.